The Relationship of Charismatic Leadership, Employee Personality, and Employee Performance: Evidence from PT. Karya Abadi Luhur - Supratman, Octaria Vadilla; Entang, Mohammad; Tukiran, Martinus (IJOSMAS, 2021)
- The purpose of this study was to determine the relationship between charismatic leadership, employee personality, and employee performance in PT. Karya Abadi Luhur. The study population was 152 employees and the sample was 111 employees. Collecting data for each variable studied using a questionnaire with a rating scale. The data analysis technique used descriptive statistical analysis techniques and inferential statistical analysis techniques. The results showed: (a) There is a positive and significant relationship between charismatic leadership and employee performance with the correlation coefficient ry.1 = 0.528 with moderate relationship strength and the regression equation Ŷ = 83.547 + 0.443X1. Charismatic leadership contribution to employee performance is 27.9%, (b) There is a significant positive relationship between personality and employee performance with a correlation coefficient of ry.2 = 0.713 with a strong relationship strength and the regression equation Ŷ = 64.022 + 1.504X2. Personality contribution to employee performance is 50.8%, and (c) There is a significant positive relationship between charismatic leadership and personality together with employee performance with a correlation coefficient of R = 0.770 with a strong relationship strength and the regression equation Ŷ = 64.597 + 0.263X1 + 1.267X2. The contribution of charismatic leadership and personality together to employee performance is 59.3%.